Wednesday

December 17, 2014

December 17, 2014

Posted by **motlhalefi** on Sunday, January 16, 2011 at 7:56am.

x2-2xy+9y2=17 solve simalteneously

- math -
**Reiny**, Sunday, January 16, 2011 at 8:48amfrom the 1st ----> x = 3y+1

(3y+1)^2 - 2y(3y+1) + 9y^2 = 17

9y^2 + 6y + 1 - 6y^2 - 2y + 9y^2 = 17

12y^2 + 4y -16 = 0

3y^2 + y - 4 = 0

(3y + 4)(y - 1) = 0

y = -4/3 or y = 1

if x = -4/3, y = 3(-4/3) + 1 = -3

if x = 1 , y = 3(1) + 1 = 4

btw, it is "simultaneously"

- correction - math -
**Reiny**, Sunday, January 16, 2011 at 9:29amYou probably figured it out yourself by at the end it should have said ...

if y = -4/3, x = 3(-4/3) + 1 = -3

if y = 1 , x = 3(1) + 1 = 4

**Answer this Question**

**Related Questions**

math - (4x-3y)2 Simplify the expression above. Which of the following is correct...

Algebra - Please look at the following simplification of an algebraic expression...

Algebra - Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a...

Math - Can 2xy - y - 1 be factored out? How? about all you can do is take the ...

Algebra - I thought number 4 on this list was incorrect but didn't know how to ...

Algebra (new one since I put "match" (bad speller) - I have a few match ...

Math - Solve. Do not use decimals. x^2+xy=3 3x^2+2xy-y^2=7

Math - Solve. Do not use decimals. x^2+xy=3 3x^2+2xy-y^2=7

Calculus - Consider the equation: x^2 - 2xy + 4y^2 = 64 Write an expression of ...

Math- Algebra - hi wat method would i use and how would i solve this system of ...